Effect of the COVID-19 Epidemic on Physical Activity in Community-Dwelling Older Adults in Japan: A Cross-Sectional Online Survey - Yamada, Minoru (J Nutr Health Aging, 2020)
OBJECTIVES: The objective of this study was to investigate changes in physical activity (PA) between January (before the COVID-19 epidemic) and April (during the COVID-19 epidemic) 2020 in community-dwelling older adults in Japan. DESIGN: Cross-sectional online survey. SETTING AND SUBJECTS: From April 23 to 27, 2020, an online survey was completed by 1,600 community-dwelling older adults in Japan. METHODS: We assessed the frailty status using the Kihon checklist, and other demographics and asked questions regarding PA at two time points: January and April 2020. We defined the total PA time (minutes) per week based on activity frequency and time. RESULTS: The study participants’ mean age, proportion of women, and prevalence of frailty were 74.0±5.6 years, 50% (n=800), and 24.3% (n=388), respectively. We found a significant decrease in total PA time in April 2020 (median [interquartile range (IQR)], 180 [0 to 420]) when compared to January 2020 (median [IQR], 245 [90 to 480]) (P<0.001). We also performed a subgroup analysis according to the frailty category; total PA time significantly decreased in April 2020 when compared to January 2020 for all frailty categories (P<0.001). CONCLUSION: In conclusion, due to the COVID-19 epidemic, the total PA time in April 2020 significantly decreased compared to that in January 2020 in older adults. This finding may lead to a higher incidence of disability in the near future in older people.